Germany's PSB going online: Is there an economic justification for Public Service Media online? - Nadine Lindstädt (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2010)
Public Service Media (PSM) online is a highly up to date topic. There is no clear consensus among researchers if Public Service Media should have a legitimization online and if so to which extent. Some authors still demand for an extensive role of public service provision in the digital era whereas others either argue against PSM on the internet at all or assign them a restrictive and complementing function at the most. The question has furthermore concerned the European Commission as well as several Member States for many years now. Public service broadcasters have been accused of distorting competition online - an area that up to then seemed to have worked being left to the market. Though the extension of public service providers towards the internet is legitimized by the European Commission it seems appropriate to analyze if there is a true economic justification for having Public Service Media online and if so to which extent. This article contributes to enter into that question against the background that the traditional public service broadcasting system (i.e. television and radio) is taken as given and unchangeable for the analysis. The paper thereby waives to repeat the fundamental discussion of pros and cons of public service provision and, instead, concentrates specifically on elaborating possible cross-media effects.
Keywords: L82; A20; L13; M21; 330; media economics; two-sided markets; competition; public service broadcasting; public service media; Rundfunksender; Rundfunkfinanzierung; Internet; Wettbewerb; Marktstruktur; Medienökonomik; Deutschland